The Utility of Endoscopic Ultrasound in Patients with Isolated Elevations in Serum Amylase and/or Lipase - Lalitha M. Sitaraman; Amit H. Sachdev; Tamas A. Gonda; Amrita Sethi; John M. Poneros; Frank G. Gress (Korean Society of Gastrointestinal Endoscopy, 2019)
Background/Aims The aim of this study was to describe the diagnostic yield of endoscopic ultrasound (EUS) in patients with isolated elevated levels of amylase and/or lipase. Methods A retrospective chart review was conducted at a large academic medical center from 2000 to 2016. Patients were selected based on having elevated amylase, lipase, or both, but without a diagnosis of pancreatitis or known pancreatobiliary disease. Patients were excluded if they had abnormal liver function tests or abnormal imaging of the pancreas. Results Of 299 EUS procedures performed, 38 met inclusion criteria. Symptoms were present in 31 patients, most frequently abdominal pain (87%). In 20 patients (53%), initial EUS most commonly found chronic pancreatitis (n=7; 18%), sludge (5; 13%), or new diagnosis of pancreas divisum (3; 8%). In the asymptomatic patients (7), 3 had a finding on EUS, most importantly sludge (2), stone (1), and pancreas divisum (1). No patients were diagnosed with a mass or pancreatic cyst. During the follow up period, 6 patients (22%) had cholecystectomy. Conclusions In our study of patients with isolated elevations in amylase and/or lipase without acute pancreatitis who underwent EUS, approximately 50% had a pancreatobiliary finding, most commonly chronic pancreatitis or biliary sludge.